COGNITIVE NEUROSCIENCE IN THE STRUCTURE OF PROFESSIONAL READINESS OF SPECIALISTS IN THE SPECIALTY A7 PHYSICAL CULTURE AND SPORTS IN HIGHER EDUCATION INSTITUTIONS (Physical Culture and Sport: Scientific Perspective, 2025)
The development of cognitive neuroscience opens new horizons for optimizing the process of professional training of physical education and sports specialists by integrating knowledge about neuroplasticity, cognitive regulation of motor activity, and psychophysiological adaptation mechanisms. This study emphasizes an interdisciplinary approach that combines sports science, cognitive psychology, neurophysiology, and modern digital technologies, shaping an innovative educational format aimed at enhancing the cognitive-motor efficiency of future professionals. The research examines the application of cognitive-motor learning, biofeedback methodologies, virtual reality technologies, and sensorimotor integration, which contribute to the improvement of professional competencies in physical education and sports. The aim of the study is to provide a theoretical substantiation and empirical analysis of the impact of cognitive neuroscience on the professional training of physical education and sports specialists through the integration of cognitive-motor methodologies, biofeedback technologies, sensorimotor integration, and adaptive neurophysiological modeling. The research seeks to develop a methodological foundation for the personalized application of cognitive technologies in sports-pedagogical activities. It has been confirmed that cognitive-oriented methods based on the mechanisms of neural network plasticity enhance the adaptive potential of athletes and educators, forming effective strategies for sensorimotor control, stress reduction, and increased cognitive productivity. The integration of neurofeedback technologies enables real-time correction of neurodynamic processes, improving concentration levels, psychophysiological regulation, and cognitive endurance. The methodological foundation of the study is based on modern neuroscience concepts that explain the relationship between physical activity and structural-functional changes in the brain. Special attention is given to the impact of cognitive training programs on the activity of the prefrontal cortex, hippocampus, and motor areas, which ensure effective decision-making, cognitive control, and spatial orientation. Additionally, the study explores the use of adaptive neurophysiological management algorithms that allow for the personalization of the educational process and enhance its effectiveness. The results indicate that cognitive-motor methods significantly improve sensorimotor integration, reaction speed, spatial orientation, and cognitive control in physical education professionals. Moreover, it has been demonstrated that such methods increase stress resilience, which is critically important for effective performance under high physical and psycho-emotional loads.
Keywords: professional training; psycho-pedagogical activity; psycho-emotional state; biofeedback technologies; neuroplasticity; cognitive-motor learning; sensorimotor integration; adaptive neurophysiological model; physical load; cognitive regulation of movement